Innovative Muhadastah Material Development by Puppet Theater for Special Needs Students Based on William Francis Mackey’s Theory - Laili Mas Ulliyah Hasan; Sutaman Sutaman; Umi Machmudah (STAI Hubbulwathan Duri, 2024)
Developing effective muhadastah (conversational/oral communication) materials for special needs, students presents ongoing challenges. This study investigates the use of Puppet Theater as an innovative tool to improve muhadastah skills in special needs students, drawing on William Francis Mackey's theory of contextual and interactive learning. This research was conducted at MTs Wachid Hasyim Surabaya and involved 11 Class VIII special needs students, including individuals with hearing and speech impairments, ADHD, slow learning, and emotional needs. A qualitative methodology was applied, employing observations, interviews, and instructional material analysis to assess the effectiveness of Puppet Theater in enhancing communication skills within Mackey’s theoretical framework. The findings indicate that Puppet Theater markedly improved student engagement, interaction, and language development. Notably, a student with a speech impairment exhibited enhanced articulation and confidence, while students with ADHD showed better focus and participation. Slow learners benefited from the structured social interactions that Puppet Theater provided, fostering their conversational skills. These results suggest that Puppet Theater aligns well with Mackey’s contextual learning principles, offering a dynamic approach for muhadastah skill development in special needs students. It fosters a conducive environment for social and linguistic growth, accommodating diverse learning needs effectively. Puppet Theater proves to be a creative and interactive method for developing muhadastah materials, highlighting its potential as an educational strategy for diverse learners. This study contributes to special education literature by demonstrating Puppet Theater's effectiveness in enhancing conversational skills, with implications for broader educational applications.